In Vitro, In Vivo and In Silico Effectiveness of LASSBio-1386, an N-Acyl Hydrazone Derivative Phosphodiesterase-4 Inhibitor, Against Leishmania amazonensis - Silva, Dahara Keyse Carvalho; Teixeira, Jessicada Silva; Moreira, Diogo Rodrigo Magalhães; da Silva, Tiago Fernandes; Barreiro, Eliezer Jesus de Lacerda; Freitas, Humberto Fonseca de; Pita, Samuel Silva da Rocha; Teles, André Lacerda Braga; Guimarães, Elisalva Teixeira; Soares, Milena Botelho Pereira (Frontiers in Pharmacology, 2020)
Leishmaniases are group of neglected diseases that affect about 12 million people worldwide. The available treatments are limited and may cause severe adverse effects, and thus, the search for new drugs more effective and less toxic is relevant. We have previously investigated the immunomodulatory effects of LASSBio-1386, an N-acylhydrazone derivative. Here we investigated the in vitro and in vivo activity of LASSBio-1386 against L. amazonensis. LASSBio-1386 inhibited the proliferation of promastigotes of L. amazonensis (IC50 = 2.4 ± 0.48 µM), while presenting low cytotoxicity to macrophages (CC50 = 55 ± 3.97 µM). In vitro, treatment with LASSBio-1386 reduced the percentage of Leishmania-infected macrophages and the number of intracellular parasites (IC50 = 9.42±0.64 µM). Importantly, topical treatment with LASSBio-1386 significantly reduced the lesion size, parasite load and histopathological alterations in BALB/c mice infected with L. amazonensis, compared to vehicle-treated control. Moreover, LASSBio-1386 caused ultrastructural changes, arrested cell cycle in G0/G1 phase and did not alter the membrane mitochondrial potential of L. amazonensis. Aiming to its possible molecular interactions, we performed docking and molecular dynamics studies on Leishmania phosphodiesterase B1 (PDB code: 2R8Q) and LASSBio-1386. The computational analyses suggest that LASSBio-1386 acts against L. major and L. amazonensis through the modulation of leishmanial PDE activity. In conclusion, our results indicate that LASSBio-1386 as a selective antileishmanial compound, being a promising molecule for drug development for the treatment of leishmaniasis.